Teori Kebangkitan Islam dan Realitasnya - Siti Afifatur Rahmawati; Uswatun Hasanah (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2015)
The following article discusses the rise of Islam, its theory and reality, which is referenced from the clash of world civilizations. There are at least three kinds of theories regarding the clash of civilizations. First, the clash of civilization theory, the two soft power theories (soft power theory), and the third constructivism theory (constructivism theory). These three theories, despite being mutually independent, can be intertwined in reality. However, of the three theories of clash of civilizations, the effect was more pronounced, which led to the rise of Islamic revival movements in various countries initiated by Jamaluddin Al-Afghani, Muhammad Abdul, Muhammad Rashid Ridho and Sayyid Quthb, which influenced all Islamic countries. The results are quite positive. Besides the muslin community realized the height of their civilization, they also realized that Western civilization was not the solution to world civilization. So that Islam was re-conceived as an alternative civilization that made human life even better, as had happened in the heyday of Islam. Of course in a different way with the previous method. So this is where the theory of soft power and constructive theory is needed to change the flow of world from materialistic to Islamic civilization.